TERRY EASTWOOD and HEATHER MACNEIL, Currents of Archival Thinking - Williams, Caroline (Archivaria, 2011)
Currents of Archival Thinking. TERRY EASTWOOD and HEATHER MACNEIL. Santa Barbara: Libraries Unlimited, 2010. 254 p. ISBN 978-1-59158-656-2.